2009
DOI: 10.1111/j.1399-302x.2008.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota on different oral surfaces in healthy children

Abstract: The results showed a pattern of colonization in children similar to that previously found in adults. Differences in the profile between age groups suggest a gradual maturation of the oral microbiota, with it being made up of an increasing number of Orange and Red complex species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 45 publications
(63 reference statements)
2
97
0
12
Order By: Relevance
“…Subgingival plaque composition of gingivitis free children presented almost the same percentage of P. gingivalis, A. actinomycetemcomitans and T. forsythensis and no statistical differences were found between the level of the above-mentioned species compared with children with gingival infl ammation [8,10,12].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Subgingival plaque composition of gingivitis free children presented almost the same percentage of P. gingivalis, A. actinomycetemcomitans and T. forsythensis and no statistical differences were found between the level of the above-mentioned species compared with children with gingival infl ammation [8,10,12].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies revealed that some of the periodontopathogenic bacteria can be present in gingival crevicular fl uid of children with healthy periodontium [8][9][10][11]. Subgingival plaque composition of gingivitis free children presented almost the same percentage of P. gingivalis, A. actinomycetemcomitans and T. forsythensis and no statistical differences were found between the level of the above-mentioned species compared with children with gingival infl ammation [8,10,12].…”
Section: Discussionmentioning
confidence: 94%
“…Gingivitis may be a non-specific bacterial infection dependent on the level of plaque present (Goodson et al, 2004). Nevertheless, the prevalence and severity of inflammation of the oral tissues (gingivitis and periodontitis) is low in healthy young children and gradually increases with increasing age (Matsson, 1993;Papaioannou et al, 2009). With increasing age, the proportions of periodontal pathogens also increase Kimura et al, 2002).…”
Section: Histopathologymentioning
confidence: 99%
“…T1 T0 T1 T0 T1 T0 T2 T0 T2 T0 T2 (Zambon, 1996;Papaioannou et al, 2009; Armitage e Cullinan, 2010) e, também, a localização do dente na arcada, além da efetividade da higiene bucal A posição de colagem dos acessórios é outro fator de inferência na alteração da microbiota e acúmulo de biofilme (van Gastel et al, 2007). Neste estudo, todos os acessórios foram colados supra-gengivalmente e no mínimo 0,5mm aquém da margem livre da gengiva.…”
Section: Resultsunclassified
“…Dentre as técnicas de biologia molecular, encontra-se a técnica checkerboard DNA-DNA hybridization, preconizada por Socransky et al, em 1994, e empregada em Odontologia nas áreas de Periodontia (Lee et al, 2005;Dahlén e Leonhardt, 2006;Gellen et al, 2007;Teles et al, 2010;Gojkov-Vukelic et al, 2013), Endodontia (Vianna et al, 2008;Siqueira e Rôças, 2009;, Implantodontia (Duarte et al, 2009;do Nascimento et al, 2009;do Nascimento et al, 2013), Odontopediatria Papaioannou et al, 2009;Peixoto et al 2011;de Oliveira et al 2014) e Cariologia Mannaa et al, 2013).…”
Section: Introductionunclassified